The Strategic Alternatives for Emerging Markets Entry Strategies of Multinational Companies and Their Main Investments in Romania - Elena ŞERBAN (Revista de Management Comparat International)
The article presents the strategic alternatives which are considered by a multinational company before deciding to enter on an emerging market. The decision is based on the long term opportunity of the selling market in the analyzed country, on the cultural and institutional differences between the multinational native and local environment, resources and business partners’ availability, as well as on the market share it can acquire since the entrance. Romania is considered one of the emerging markets in Central and Eastern Europe. During the past two decades, certain industries like telecommunications, FMCG, oil and energy, construction, finance and banks, pharma and IT represented the main targets regarding market entrance and development for the big international players. 107 companies were investigated. For seven of them we had to repeat investigation because of inconsistencies in responses. There were no refusals of questionnaires.